Recovery kinetics following sprint training: resisted versus unresisted sprints - Christina A. Liakou; Ioannis G. Fatouros; Athanasios Poulios; Themistoklis Tsatalas; Evangeli Karampina; Panagiota Karanika; Despoina Kaloudi; Anastasia Rosvoglou; Panagiotis Tsimeas; Anna Kamperi; Niki Syrou; Athanasios Gatsas; et al. (European Journal of Applied Physiology, 2024)
Purpose To determine the recovery kinetics of performance and exercise-induced muscle damage following different sprint-training protocols. Methods In a crossover design, ten male and female athletes (20.6 ± 2.4 years) performed 2 × (3 × 20 m: 2 min rest) and 1× (3 × 30 m: 3 min rest) of: (a) unresisted sprints (UST), (b) resisted sprints with 10% of body mass (BM) load (RST10), (c) resisted sprints with 20% BM load (RST20), against a control trial (no-training). Results Blood lactate (mmol/L) increased post-training versus pre-training in all sprint-training trials (6.7 ± 2.4 vs 1.2 ± 0.2, 5.6 ± 2.4 vs 1.3 ± 0.3, 7.3 ± 2.7 vs 1.2 ± 0.3, in UST, RST10, RST20, respectively), as did creatine kinase (U/L) 24 h, 48 h and 72 h post-training (UST: 251 ± 173, 238 ± 154, 209 ± 115 vs 155 ± 9, RST10: 252 ± 134, 240 ± 83, 218 ± 103 vs 164 ± 106; RST20: 237 ± 133, 323 ± 303, 262 ± 184 vs 179 ± 106, respectively). DOMS of knee-extensors (KE) and knee-flexors (KF) increased post-training up to 72 h in all sprint-training trials versus pre-training (ranging from 1.6 ± 1.3 to 3.8 ± 2.8 vs 1.0 ± 0, respectively). Eccentric torque (N m) of the KE of the non-dominant limb, decreased 24 h post-training versus pre-training in all sprint-training trials (UST: 249 ± 49 vs 266 ± 54; RST10: 229 ± 52 vs 273 ± 72; RST20: 253 ± 6 vs 262 ± 56), as did that of the KF of the dominant limb (UST: 135 ± 29 vs 144 ± 26; RST10: 130 ± 29 vs 140 ± 25; RST20: 139 ± 33 vs 142 ± 26). 10-m sprint-time (s) increased 48 h post-training versus pre-training (1.81 ± 0.15 vs 1.77 ± 0.11), and 30-m sprint-time increased 24 h, 48 h, 72 h post-training versus pre-training (4.35 ± 0.36, 4.40 ± 0.44, 4.33 ± 0.41 vs 4.21 ± 0.34, respectively), only in RST20. Conclusions Unresisted and resisted sprint-training induces prolonged reduction of muscle strength (24 h), and sprinting performance (72 h), associated with prolonged increase of DOMS and CK (72 h).